Patterns of HIV Risks and Related Factors among People Who Inject Drugs in Kermanshah, Iran: A Latent Class Analysis - Sharifi, H.; Mirzazadeh, A.; Noroozi, A.; Marshall, B.; Farhoudian, A.; Higgs, Peter; Vameghi, M.; Mohhamadi Shahboulaghi, F.; Qorbani, M.; Massah, O.; Armoon, B.; Noroozi, M. (2017)
Â© 2017 Taylor & Francis Group, LLC. The objective of this study was to explore patterns of drug use and sexual risk behaviors among people who inject drugs (PWID) in Iran. We surveyed 500 PWID in Kermanshah concerning demographic characteristics, sexual risk behaviors, and drug-related risk behaviors in the month prior to study. We used latent class analysis (LCA) to establish a baseline model of risk proï¬?les and to identify the optimal number of latent classes, and we used ordinal regression to identify factors associated with class membership. Three classes of multiple HIV risk were identified. The probability of membership in the high-risk class was 0.33, compared to 0.26 and 0.40 for the low- and moderate-risk classes, respectively. Compared to members in the lowest-risk class (reference group), the highest-risk class members had higher odds of being homeless (ORÂ =Â 4.5, CI: 1.44â€“8.22; pÂ =Â 0.001) in the past 12Â months. Members of the high-risk class had lower odds of regularly visiting a needle and syringe exchange program as compared to the lowest-risk class members (AORÂ =Â 0.42, CI: 0.2â€“0.81; pÂ =Â 0.01). Findings show the sexual and drug-related HIV risk clusters among PWID in Iran, and emphasize the importance of developing targeted prevention and harm reduction programs for all domains of risk behaviors, both sexual and drug use related.